Population, resources and environment a framework of interrelationships - Cabrido, Candido A. (1989)
A framework for expressing and understanding the interlocking relationships between population, resources and environment within a dynamic system is presented in this paper. The framework takes into account the immediate, intermediate and long-term behavior of the system under the assumption that the quality of the variable relationships determines the quality of the environment and of life. The main hypothetical model presented portrays the system's behavior under sustainable and non-sustainable development, with the concept of sustainability being conceived as multi-dimensional and anchored on the concept of carrying capacity. Aside from the main model presented, the author also presented hypothetical models/scenarios on: the effect of exceeding the maximum sustainable production level"; population oscillation about the carrying capacity threshold level; the impact of conservation measures on renewable resources; the impact of recycling and substitution on nonrenewable resources; and the determination of potential surplus production of a given resource.
The need for a framework -- the framework -- Conclusion.
Photocopy.
Paper presented to the Roundtable Discussions on "Environment and Development" sponsored by the Program Committee of the Second National Social Science Congress, which was held at the Philippine Social Science Center, U.P. Diliman, Quezon City on July 13, 1988.
Keywords: Environmental policy -- Philippines; Natural resources -- Philippines; Philippines -- Population